Rational design of coaxial structured carbon nanotube–manganese oxide (CNT–MnO2) for energy storage application. (30th April 2015) - Salunkhe, Rahul R; Ahn, Heejoon; Kim, Jung Ho; Yamauchi, Yusuke
Abstract: Recently, there has been great research interest in the development of composites (core–shell structures) of carbon nanotubes (CNTs) with metal oxides for improved electrochemical energy storage, photonics, electronics, catalysis, etc. Currently, the synthetic strategies for metal oxides/hydroxides are well established, but the development of core–shell structures by robust, cost-effective chemical methods is still a challenge. The main drawbacks for obtaining such electrodes are the very complex synthesis methods which ultimately result in high production costs. Alternatively, the solution based method offers the advantages of simple and cost effective synthesis, as well as being easy to scale up. Here, we report on the development of multi-walled carbon nanotube–manganese oxide (CNT–MnO2 ) core–shell structures. These samples were directly utilized for asymmetric supercapacitor (ASC) applications, where the CNT–MnO2 composite was used as the positive electrode and ZIF-8 (zeolitic imidazolate framework, ZIF) derived nanoporous carbon was used as the negative electrode. This unconventional ASC shows a high energy density of 20.44 W h kg −1 and high power density of 16 kW kg −1 . The results demonstrate that these are efficient electrodes for supercapacitor application.